Madagascar's EPI vaccine programs: A systematic review uncovering the role of a child's sex and other barriers to vaccination - Hahesy, Emma; Cruz-Espinoza, Ligia Maria; Nyirenda, Gabriel; Tadesse, Birkneh Tilahun; Kim, Jerome H.; Marks, Florian; Rakotozandrindrainy, Raphael; Wetzker, Wibke; Haselbeck, Andrea (Frontiers in Public Health, 2022)
Background: Immunizations are one of the most effective tools a community can use to increase overall health and decrease the burden of vaccine-preventable diseases. Nevertheless, socioeconomic status, geographical location, education, and a child’s sex have been identified as contributing to inequities in vaccine uptake in low- and middle-income countries (LMICs). Madagascar follows the World Health Organization’s Extended Programme on Immunization (EPI) schedule, yet vaccine distribution remains highly inequitable throughout the country. This systematic review sought to understand the differences in EPI vaccine uptake between boys and girls in Madagascar. Methods: A systematic literature search was conducted in MEDLINE, the Cochrane Library, Global Index Medicus, and Google Scholar to identify articles reporting sex-disaggregated vaccination rates in Malagasy children. Gray literature was also searched for relevant data. Sex-disaggregated data were synthesized to understand the impact of a child’s sex on vaccination status. Findings: The systematic search identified 585 articles of which a total of three studies were included in the final data synthesis. One additional publication was included from the gray literature search. Data from included articles were heterogeneous and, overall, indicated similar vaccination rates in boys and girls. Three of the four articles reported slightly higher vaccination rates in girls than in boys. Interpretation: The systematic review revealed the scarcity of available sex-stratified immunization data for Malagasy children. The evidence available was limited and heterogeneous, preventing researchers from conclusively confirming or denying differences in vaccine uptake based on sex. A more comprehensive assessment of sex-disaggregated vaccination status of Malagasy children and its relationship with additional obstacles to vaccination is recommended to further investigate potential differences in vaccination status.